Beneficial effects of the mixed adjuvant of CpG plus monophosphoryl lipid a in immunization with a recombinant protein vaccine for hepatitis A - Hwang, Inkyu; Choi, Daewoon; See, Hyejeong; Kim, Wonyong; Chung, In Sik; Shon, Dong-Hwa (Applied biological chemistry, 2013)
In an effort to develop a new vaccine for hepatitis A, which is mainly transmitted via contaminated foods and water, recombinant virus protein 1 (VP1) of hepatitis A virus was used as an antigen. Several adjuvants in a single or a mixed form, i.e., alum, CpG oligodeoxynucleotide, monophosphoryl lipid A (MPL), alum plus MPL, and CpG plus MPL, were also tested for their immunological properties. When their effects on the production of VP1-specific IgG relative to that of total IgG and the levels of and balance between Th1- and Th2-type cytokine productions were compared, CpG plus MPL was found to have highly beneficial effects, providing a new insight in selection of adjuvant for development of a new vaccine.